Empowering women through local learning programs: A case study of the PUTARAN initiative in East Java, Indonesia - Berlian Fauzia Maylani; Lukman Arif (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
This study explores the process of women's empowerment through the PUTARAN program (Women's Empowerment Learning Center), initiated by the DP3AK of East Java Provincial Government. The research is motivated by the persistent structural barriers faced by women, including limited access to resources, gender-based violence, and restricted participation in public spaces. The study examines how a state-run, learning-based empowerment program facilitates personal and social transformation among marginalized women. A qualitative interpretive case study design was employed, with data collected through in-depth interviews, participant observation, and document analysis. The findings reveal a multidimensional transformation process unfolding across three stages: critical awareness, capacity enhancement, and intellectual empowerment. Participants reported increased self-awareness, social agency, economic resilience, and digital literacy. This study contributes to the empowerment literature by offering a novel application of Freire’s conscientization, Kabeer’s theory of resources and agency, and Sen’s capability approach within a localized public-sector initiative in Indonesia. Unlike previous studies focusing on NGO-based interventions, this research highlights the transformative potential of state-led programs when combined with dialogical learning and institutional support. The study concludes that integrating contextual learning, inclusive governance, and digital capacity-building constitutes an effective and sustainable women empowerment strategy. Policy implications include providing access to microfinance, post-training mentoring, advanced digital literacy training, establishing women-led business networks, and replicating the program in other regions through standardized curricula and cross-sectoral support. Thus, PUTARAN represents a state-led model of women’s empowerment that is responsive, participatory, and sustainable.   Penelitian ini mengeksplorasi proses pemberdayaan perempuan melalui program PUTARAN (Pusat Pembelajaran Pemberdayaan Perempuan) yang diselenggarakan oleh DP3AK Provinsi Jawa Timur. Latar belakang penelitian ini adalah masih kuatnya hambatan struktural yang dihadapi perempuan, seperti ketimpangan akses terhadap sumber daya, kekerasan berbasis gender, dan keterbatasan partisipasi dalam ruang publik. Studi ini bertujuan untuk menganalisis bagaimana program pemberdayaan berbasis pembelajaran tersebut memfasilitasi transformasi personal dan sosial peserta perempuan. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus interpretatif, dan data dikumpulkan melalui wawancara mendalam, observasi, serta dokumentasi program.Temuan mengungkapkan bahwa program PUTARAN berhasil mendorong transformasi multidimensional melalui tiga tahap: penyadaran kritis, peningkatan kapasitas, dan penguatan intelektual. Peserta mengalami peningkatan signifikan dalam kesadaran diri, agensi sosial, keterampilan ekonomi, serta literasi digital. Penelitian ini berkontribusi terhadap literatur pemberdayaan dengan menawarkan aplikasi lokal dari teori Paulo Freire (conscientization), Naila Kabeer (resources and agency), dan Amartya Sen (capability approach) dalam program berbasis kebijakan publik daerah. Berbeda dari studi sebelumnya yang banyak berfokus pada intervensi NGO, studi ini menunjukkan bahwa model pemberdayaan berbasis negara juga dapat bersifat transformatif jika didukung oleh pendekatan dialogis dan dukungan kelembagaan.Kesimpulan dari studi ini menekankan pentingnya integrasi antara pembelajaran kontekstual, struktur kelembagaan yang inklusif, dan penguatan digital sebagai strategi pemberdayaan perempuan yang berkelanjutan. Implikasi kebijakan mencakup penyediaan akses permodalan mikro, pendampingan pasca pelatihan, pelatihan literasi digital lanjutan, pembentukan jaringan usaha perempuan, serta replikasi program di daerah lain dengan standarisasi kurikulum dan dukungan lintas sektor. Sehingga, PUTARAN menjadi model pemberdayaan perempuan berbasis negara yang responsif, partisipatif, dan berkelanjutan.